2017
DOI: 10.1161/jaha.117.006259
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Disease Measures and Left Ventricular Structure and Function: The Atherosclerosis Risk in Communities Study

Abstract: BackgroundHeart failure is one of the most important complications of chronic kidney disease (CKD). However, few studies comprehensively investigated left ventricular (LV) structure and function in relation to 2 key CKD measures, estimated glomerular filtration rate (eGFR) and urine albumin/creatinine ratio (ACR).Methods and ResultsAmong 4175 ARIC (Atherosclerosis Risk in Communities) participants (aged 66–90 years during 2011–2013), we quantified the association of eGFR and ACR with echocardiogram parameters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 43 publications
(40 reference statements)
1
22
0
2
Order By: Relevance
“…The patients were divided into two groups according to renal function, the renal dysfunction is defined as eGFR < 90 mL/min·1.73 m 2 [14]. 182 patients (54.2%) had renal dysfunction and 154 patients (45.8%) did not have renal dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…The patients were divided into two groups according to renal function, the renal dysfunction is defined as eGFR < 90 mL/min·1.73 m 2 [14]. 182 patients (54.2%) had renal dysfunction and 154 patients (45.8%) did not have renal dysfunction.…”
Section: Methodsmentioning
confidence: 99%
“…The results of the present study have shown that albuminuria is an independent predictor of LVH in CKD patients. A recent study reported that higher ACR was associated with LV mass, size, systolic function, and diastolic function in CKD patients [ 37 ]. This finding is in agreement with a previous international collaborative study showing a similar pattern for clinical risk of heart failure [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that the hypertension, DM and renal function were associated with the impaired LV diastolic function ( 8 , 11 , 30 ). Although the univariable logistic analysis showed that the hypertension, DM and eGFR were associated with LV diastolic dysfunction, this associations disappeared in multivariable logistic analysis.…”
Section: Discussionmentioning
confidence: 96%